Occupational health professionals’ and HR specialists’ perceptions of telemental health services in occupational health care settings: A qualitative study - Elina Kervinen; Lauri Vähätalo; Anna Siukola; Tiia Reho; Klas Winell; Riitta Sauni (Digital Health)
Objective The rise in mental health-related work disability pensions highlights the need for more research on how occupational health care (OHC) can support mental health, including the use of telehealth (TH) services in mental health care. Methods The research, employing a descriptive qualitative approach through interviews ( n  = 42), focused on experiences of professionals from a private OHC service provider in Finland and human resource representatives (HRRs) of OHC client companies. Inductive content analysis was used to analyze the data. Results Our research suggests that TH services provided by OHC can enhance access to care and expedite the initiation of work ability support, particularly in mental health cases. However, potential challenges include a perceived sense of distance, superficiality in interactions, and difficulty in forming a comprehensive understanding due to few non-verbal cues. Conclusion A combined approach of TH and face-to-face services is suggested to provide flexible, and individualized support. Further studies on remote low-threshold discussion mental health services and studies comparing TH and face-to-face services are advised.